A Study Of Influence Of Corporate Social Responsibility (CSR) Activities Of Firms In Consumer Purchasing Decision In Malaysia - Ahmad, Mashuk (2003)
Most of the corporate social responsibility (CSR) studies conducted so far have been in the context of developed countries. Very few studies are available on the CSR practices in Malaysia which are in the context of company perspective. No study was found about CSR from the consumer’s point of view conducted in Malaysia. Since consumers are the real contributors to the firm’s revenue and profit, it is important to learn about their views on the practices of CSR. Research in this area is particularly important as it will provide greater insight on the extent of CSR among Malaysians. It will also show the changing attitudes of consumers towards CSR in a developing country like Malaysia. Further, this research may provide implications on the concept of CSR among the consumers in Malaysia, a developing country, which may have different meanings of CSR compared to the consumers of the developed countries – specially the Western countries. This paper reports the findings from the Malaysian consumers to determine their views concerning the social responsibilities of companies, which may influence the purchasing decision of the consumers.